IMPLEMENTASI GREEN SCHOOL PADA PAUD TUNAS BANGSA NGAJUM - Cahyana, M. Wahid; Muhklisin, Muh. Irfan; Wulandari, Dewi Tri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The teaching and learning process is based on a quality education system, one of the stages to achieve the above is by creating a comfortable school atmosphere, by implementing Green School. But in practice there are still many schools that have not implemented greening programs in their schools even though the government has socialized the importance of reforestation in schools from an early age, in order to get cool air and a good environment. In the Petungroto hamlet there is only one Tunas Bangsa ECD and has not implemented greening with various types of plants, these plants are placed in the school environment to provide comfort during the teaching and learning process and introduce plants to children from an early age. For this reason, there is a need for assistance in managing Green School-based PAUD in Petungroto Hamlet, Babadan Village, Ngajum District, Malang Regency. In addition to realizing greening in the PAUD environment, activation assistance for waste bank management is carried out so that it can be guaranteed to improve people's lives from various health and economic aspects. The method used in KKN-PPM activities is (1) Implementation of Green School by utilizing existing resources wisely, (2) Management of Waste Bank from the garbage collection process, sorting the recording and sale of waste bank results. The target and outcome to be achieved from the KKN-PPM activities is to make PAUD Tunas Bangsa as a Green School, introducing the types and benefits of plants to children. Village officials and the community can understand the importance of reforestation and the benefits of the Waste Bank for the environment in Petungroto Hamlet, Babadan Village, Kec. Ngajum.